Studi Geologi Teknik Tapak Penyimpanan Akhir Limbah Radioaktif (LRA) Demo Plant Tipe NSD Kedalaman Menengah di Puspiptek, Serpong - Syaeful, Heri; Sucipta, Sucipta; Sadisun, Imam Achmad (EKSPLORIUM, 2014)
Final disposal of radioactive waste intended to keep radioactive substances does not released to the environment until the substance activity decreased to the safe level. Storage concept of radioactive waste (RAW) final disposal that will be developed at the area of Puspiptek, Serpong is near surface disposal (NSD). Based on depth, NSD divided on two type, near surface NSD and medium depth NSD. Concept NSD in this research is medium depth NSD, which is between 30–300 meters. During NSD construction in medium-depth required the works of sub-surface excavation or tunneling. Analysis of in-situ stresses and sub-surface deformation performed to recognize the stress magnitude and its distribution that developed in soil/rock as well as the deformation occurred when sub-surface excavation takes place. Based on the analysis, acknowledged the magnitude of tensional and compression stress and its distribution that range from -441 kPa to 4.028 kPa with values of natural deformation or without reinforcement between 4.4 to 13.5 cm. A rather high deformation value which is achieved 13.5 cm leads to necessity of engineering reinforcement during excavation. The designs of engineering reinforcement on every excavation stage refer to the result of modeling analysis of stress and deformation distribution pattern.